A critique of Kwasi Wiredu’s humanism and impartiality - Molefe, Motsamai (University of the Free State, 2016)
This article offers a critical reflection on Kwasi Wiredu’s moral theory. On the one hand, the article is concerned with the meta-ethical question regarding the nature of moral properties, specifically, whether they are physical (natural) or spiritual (supernatural). On the other, I reflect on one facet of Wiredu’s normative theory, namely, whether morality is best captured by partiality or impartiality in the African tradition. With regards to meta-ethics, this article reflects that Wiredu’s rejection of a spiritual (supernaturalist) foundation of African ethics is unsatisfactory; I also contend that he does not offer a satisfactory defence of physicalism. I conclude by observing that a plausible meta-ethical theory, either physicalist or religious, is yet to be elaborated within the African tradition. Secondly, I argue that Wiredu’s normative theory is characterised by a feature – impartiality – that is at odds with much of African moral intuitions. Assertions like ‘charity begins at home’ seem to suggest that African ethics should be read in terms of partiality rather than impartiality.
Keywords: Humanism; Kwasi Wiredu; Impartiality; Physical (natural); Spiritual (supernatural); African ethics; Moral theory